Evaluating the efficacy of commonly used antimicrobials in the beef industry for controlling shiga toxin-producing Escherichia coli contamination on chilled beef subprimals and pre-rigor carcass sides - Krug, Matthew D. (Kansas State University, 2017)
Shiga toxin-producing E. coli (STEC) are frequently associated with foodborne illness outbreaks, especially attributable to beef. Intervention methods, such as water washes and organic acid application, are widely implemented across the beef industry to combat this risk. This research evaluates the efficacy of intervention methods applied to chilled beef subprimal pieces and pre-rigor beef carcasses to reduce STEC contamination. Beef strip loins were inoculated (ca. 5 log CFU/cm²) with a 7-serotype STEC cocktail and sprayed with increasing concentrations of peracetic acid (200-1800 ppm; ambient temperature), lactic acid (3-10%; 55°C), or a water control before being vacuum-packaged and stored for 24 h at 4°C. Meat surface excision samples and color readings (L*, a*, and b*) were obtained from each subprimal at three sampling points: post-inoculation, 5 min post chemical spray, and post-24 h vacuum packaged chilling. Peracetic acid spray and lactic acid spray reduced STEC populations by 0.5 -1.3 log CFU/cm² and 0.2 – 0.7 log CFU/cm², respectively, across the incremental concentration increases. All concentrations of peracetic acid and lactic acid concentrations ≥3.5% reduced (P ≤ 0.05) STEC populations compared to their respective control. Application of higher concentrations of lactic acid (7-10%) decreased (P ≤ 0.05) L* and b* values compared to the control, indicating that quality attributes of the subprimals were negatively effected. Carcass intervention methods were evaluated using a three-stage commercial carcass washing cabinet (Chad Equipment). Four pre-rigor carcass sides were inoculated by electrostatically spraying with a 7-serogroup STEC cocktail (ca. 6.5 log CFU/100 cm²). Three treatments were applied, in order, to each side: ambient water wash, hot water wash (82-92°C at the nozzle head), and antimicrobial mist. Meat surface excision samples were taken from the bottom, middle, and top section of each carcass side at five sampling points: 30 min post-inoculation, post-ambient water wash, post-hot water wash, post-antimicrobial spray, and after 18 h spray chilling. The combination of the high-volume ambient water wash stage and subsequent hot water wash stage reduced STEC populations on sides by 3.5, 4.7, and 4.8 log CFU/100 cm² at the bottom, middle, and top of the carcass, respectively. Due to STEC populations declining to very low or undetectable levels after the hot water stage, minimal additional STEC reductions were observed after chemical spray application and chilling. Sequential antimicrobial treatments applied using a three-stage Chad carcass wash cabinet and a subsequent chill step reduced STEC populations on pre-rigor beef carcasses by 4.5 – 5.3 log CFU/100 cm².
Keywords: Antimicrobial interventions; Beef subprimals; Beef carcasses